(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Public-private partnerships are an approach that has beenused in provision of affordable housing in the United States, as well as in anumber of other countries, since the 1980s. In these partnerships, privatedevelopers, non-profit agencies, and in some cases religious agencies receivesome funds or support from the municipal, state, or federal government (or allthree, in some cases) in order to build or renovate and manage affordablehousing. This can be used both for rental housing and as a means of encouraginglow-income home ownership. This is also an approach that has been used in anumber of other countries. However, the effectiveness of public-privatepartnerships in the management of affordable housing is not a matter ofuncontroversial agreement, and in fact has been challenged by a number ofdifferent research studies. By focusing research on a single city that has usedpublic-private partnerships in managing affordable housing, the researchproposed will attempt to identify specific issues within the public-privatepartnership and gauge its effectiveness in this city.